A Model for Word and Context Identification and Disambiguation - Aranha, Christian Nunes; Freitas, Maria Cláudia de; Dias, Maria Carmelita Pádua; Passos, Emmanuel Lopes (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
This paper focus on the interpretation of polisemic words and contexts. It suggests that this interpretation is context-sensitive, regardless of the inner representation of the words themselves. Context is viewed as a cluster formed by a target-word and the words co-ocurring with it. This cluster is achieved by means of statistical treatment of texts as well as graphs representing data obtained in the processing. Preliminary results show that this kind of approach is promising in terms of polisemic words disambiguation.